Geospatial assessment of land suitability for oil palm (Elaeis guineensis Jacq.) growing in Northern Uganda. - Anjo, Abraham; Bamweyana, Ivan (African Journals Online (AJOL), 2022)
Under the second phase of the National Oil Palm Project, the Government of Uganda plans to extend the oil palm project to Northern Uganda. According to the Final Project Design Report (2017) of the National Oil Palm Project, and based on the rainfall, soil and temperature of the region, areas in Northern Uganda have already been mapped for the project. However, no detailed information on the degree of suitability of the areas has been provided. In this research, other parameters such as land cover, elevation and slope were identified through the literature review. Furthermore, on the basis of the reclassify tool in ArcMap 10.8, the data were then reclassified into four classes, namely, highly suitable (S1), moderately suitable (S2), marginally suitable (S3) and unsuitable (N.) With the aid of the Analytical Hierarchical Process (AHP), pairwise comparison matrices were constructed and the weight of each parameter was computed. The suitability map obtained from a weighted linear combination identified 38.18%, 35.54%, 21.41% and 4.87% of the land area as highly suitable, moderately suitable, marginally suitable and unsuitable, respectively. A geospatial assessment of the suitability of the land for oil palm growing was carried out. It was based on only the soil types, but excluded the chemical properties of the soil. Therefore, further research on the chemical properties of the soils at suitable sites should be carried out. In-depth research should be carried out While considering social and economic factors among the criteria to determine the willingness and financial capability of the people to venture into oil palm growing as a source of income, Oil Palm Uganda Limited should conduct in-depth research into this issue.